Isolation and Identification of some Fungal Species from Common carp (Cyprinus carpio Linnaeus, 1758) in Taqtaq District in Erbil Province, Kurdistan Region, Iraq. - Hussein H. Mala; Shamall M. A. Abdullah (Zanco Journal of Pure and Applied Sciences)
In this study, a sample of 220 common carp (Cyprinus carpio Linnaeus 1758) was obtained from two distinct ponds in the Taqtaq District, situated in the northeastern region of Erbil Province, Kurdistan Region, Iraq. Specifically, 98 specimens were sourced from Pond A, while 122 were collected from Pond B., between September 2021 and April 2022. The fish underwent examination to determine the presence of fungal infections. The study identified eight species of fungi through morphological analysis of colony characteristics, specific growth media, and the VITEK II compact system (Biomerieux-USA). This research marks the initial documentation of five fungal species (Aspergillus flavus, Naganishia albidus, Penicillium vermiculatus, Cystobasidium minutum, and Sporothrix schenckii) infecting common carp in Iraq. Additionally, three fungal species (Aspergillus fumigatus, Aspergillus niger, and Saprolegnia parasitica) were reported for the first time in common carp within the Kurdistan Region.